Sephirot – Il Gioco: passaggio tra rappresentazione e simulazione (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
Based on Huizinga's theory of Homo Ludens, the study case I propose is SEPHIROT - THE GAME©, a method of creation for interactive performances I created in 2018, after a careful study of hypertextual narrative structures. The project is born to enhance the role of the audience as a "co-creator" of the show, making the use of recent technologies such as VR and AR on algorithmic textual structures possible, even through online streaming. My goal is to overturn the traditional composition of a performance, giving the audience a chance to actively change its form. The connection between Theatre and Game is not new, but there are still some reticences. The necessity to create interactive performances based on interactivity, hipermediality, hipertextuality and procedurality was born from these premises.
Keywords: Game, interactivity, hypermediality, hypertextuality, procedurality.